ANALYSIS OF INTERNAL AND EXTERNAL FACTORS ACCOUNTABILITY OF VILLAGE FUND MANAGEMENTSurvey of all villages in Kulon Progo Regency Yogyakarta Special Region (DIY) - Bambang Jatmiko; Androw Henky Fernanda; Titi Laras (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The purpose of this study is to test and empirically demonstrate the following: a) The impact of internal factors on village fund management in every village within Kulon Progo Regency, Special Region of Yogyakarta; b) The impact of external factors on village fund management in every village within Kulon Progo Regency, Special Region of Yogyakarta. Regarding the issues with this study, Sri Sultan Hamengkubuwono IX, the Governor of DIY, voiced his concern about the rising number of fraud cases that are taking place in the villages of Kulon Progo Regency, DIY, citing antarnews.com (2019). Enhancing village administration is necessary to raise the integrity of village governance and, in the end, provide accountability for the best possible use of community funds. What is this researcher's. This study employs a survey methodology using a questionnaire as a tool. Purposive sampling, or sampling with specific considerations and no generalizations, is used in the side technique. Purposive sampling was used to pick 122 village apparatus respondents for the sampling, and Statistical Product and Service Solutions (SPSS) v.22 software was used to handle the data. This study's findings demonstrate that: a) village officials, apparatus competency, internal control systems, and organizational commitment of the village government are internal factors that positively impact the accountability of village fund management in all villages of Kulon Progo Regency, Special Region of Yogyakarta; b) community participation is an external factor that positively influences the accountability of village fund management in all villages of Kulon.